2021
DOI: 10.1007/s00264-020-04922-1
|View full text |Cite
|
Sign up to set email alerts
|

Why compromise the patella? Five-year follow-up results of medial patellofemoral ligament reconstruction with soft tissue patellar fixation

Abstract: Purpose This study investigates the redislocation rate and functional outcome at a minimum follow-up of five years after medial patellofemoral ligament (MPFL) reconstruction with soft tissue patellar fixation for patella instability. Methods Patients were retrospectively identified and knees were evaluated for trochlea dysplasia according to Dejour, for presence of patella alta and for presence of cartilage lesion at surgery. At a minimum follow-up of five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
3
2
0
Order By: Relevance
“…In the current study, post-operative Tegner activity level was signiicantly lower than pre-injury levels. It is important to recognize that this comparison is between pre-injury and post-operative activity level and is in line with the literature, which reports a decrease in Tegner score between 0.1 and 1 point over this time period [1,3,4,13,16]. In contrast, several published studies have demonstrated an improvement in Tegner scores between 0.2 and 3.5 points following MPFL reconstruction when the comparison is made to activity level after initial injury, but prior to reconstruction [9,21,27].…”
Section: Discussionsupporting
confidence: 79%
“…In the current study, post-operative Tegner activity level was signiicantly lower than pre-injury levels. It is important to recognize that this comparison is between pre-injury and post-operative activity level and is in line with the literature, which reports a decrease in Tegner score between 0.1 and 1 point over this time period [1,3,4,13,16]. In contrast, several published studies have demonstrated an improvement in Tegner scores between 0.2 and 3.5 points following MPFL reconstruction when the comparison is made to activity level after initial injury, but prior to reconstruction [9,21,27].…”
Section: Discussionsupporting
confidence: 79%
“…The overall good outcome after MPFL reconstruction with restored function and improving WORMS scores over time is in line with previous studies that assessed clinical outcomes after isolated MPFL reconstruction [40][41][42]. Clinical KOOS and Kujala scores are similar to previously published outcomes [43][44][45].…”
Section: Discussionsupporting
confidence: 89%
“…Potentially, the stress reduction is inferior in those patients with persistent joint abnormalities. It was previously reported that trochlear dysplasia is the most common anatomic risk factor for patellar redislocation after primary isolated MPFL reconstruction followed by increased maltracking, while tunnel positioning had no significant influence [20,40]. In the present study, besides trochlear dysplasia parameters and TTTG distance, postoperatively persistent high lateral patellar tilt was identifyed as a risk factor for progressive knee joint degeneration after surgery.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Dislocation episodes also may lead to articular cartilage lesions, osteochondral fractures, and overall knee dysfunction [7, 20, 23]. Thus, MPFL reconstruction (MPFLR) is often indicated to prevent recurrent instability [1, 2, 6, 14, 28].…”
Section: Introductionmentioning
confidence: 99%